Pengaruh Kualitas Makanan, Kualitas Layanan dan Harga Terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Mediasi - Maretha Intan Puteri; Desy Prastyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of the restaurant business is currently very rapid, especially with the emergence of various new businesses with various concepts. In the face of intense competition, restaurants need to understand their weaknesses and develop the right operational strategies and marketing policies to increase customer satisfaction. This study aims to fill the knowledge gap about the role of customer satisfaction on customer loyalty, food quality, service quality and price. The population in this study consisted of Solaria customers in the Tangerang area. While the research sample was taken using purposive sampling technique with a total of 205 respondents. This research is a quantitative study that uses the Structural Equation Model - Partial Least Square (SEM-PLS) method. The results showed that food quality and price positively affect customer loyalty either directly or indirectly through customer satisfaction. Furthermore, service quality has a direct positive effect on customer satisfaction and customer loyalty. Then, customer satisfaction positively affects customer loyalty. And customer satisfaction is not proven to mediate the relationship between service quality and customer loyalty. After conducting research, the author suggests expanding the population of respondents from various regions so that researchers can compare the results between customer areas from various regions.